The Effects of Human Resources Quality, Infrastructure, Leadership, and Communication on E-Government Implementation: A Case of Indonesia Local Government - Yorri Nedy Kumajas (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This research aimed to examine the effects of human resources quality, infrastructure, leadership, and communication on e-government implementation. It used statistical methods and multiple regression analysis to figure out the relationships between variables. Data collection was conducted through observation, questionnaire survey, and literature study or documentation. By applying Slovin’s formula to determine the sample size, 245 respondents were obtained from a population of local public officers in the Yapen Islands Regency of Papua. The results show that human resources quality and communication had significant effects on e-government implementation, while infrastructure and leadership did not affect e-government implementation.